2023
DOI: 10.1021/acs.chemmater.3c02063
|View full text |Cite
|
Sign up to set email alerts
|

Amplifying the Negative Solvatochromism of Pyridinium Phenolates via Fluorene Conjugation

Irina Zharinova,
Nicolau Saker Neto,
Wallace W. H. Wong

Abstract: New chromophores carrying a donor phenolate group and an acceptor pyridyl moiety separated by a fluorene spacer are reported. A progressive elongation of the systems was achieved by the introduction of an additional phenyl ring and one or two vinyl linkers using Suzuki−Miyaura or Horner−Wadsworth−Emmons couplings. Zwitterionic forms FL1−FL5 of these donor−bridge−acceptor molecules were generated through consequent N-methylation and deprotonation reactions leading to large redshifts in absorbance maxima. UV−vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Our recent studies on the behaviour of the more conjugated OPP dyes with fluorene bridges showed improved solvatochromism compared to the phenylene analogues. [13] Given the solvatochromism of the πextended betaine dyes reported in this paper, it is proposed that the sensitivity to solvent polarity could be increased by replacing the biphenyl bridge with a fluorene unit.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Our recent studies on the behaviour of the more conjugated OPP dyes with fluorene bridges showed improved solvatochromism compared to the phenylene analogues. [13] Given the solvatochromism of the πextended betaine dyes reported in this paper, it is proposed that the sensitivity to solvent polarity could be increased by replacing the biphenyl bridge with a fluorene unit.…”
Section: Discussionmentioning
confidence: 97%
“…Thin layer chromatography was performed on Merck-Millipore Silica gel 60G F 254 glass plates, and spots were revealed under 254 nm and 365 nm light from a mercury lamp. 1 H-NMR and 13 C-NMR spectra were obtained on a 500 MHz Bruker spectrometer, and shifts were referenced to the NMR solvent signals. Mass spectra were obtained on a Thermo Exactive Plus Orbitrap ESI-MS spectrometer operating in positive or negative mode.…”
Section: Experimental Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation